1997
DOI: 10.1074/jbc.272.43.26918
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Sp1 Binding Activity in Human Chondrocytes and Its Alterations during Chondrocyte Dedifferentiation

Abstract: We have detected DNA binding activity for a synthetic oligonucleotide containing an Sp1 consensus sequence in nuclear extracts from human chondrocytes. Changes in the levels of Sp1 oligonucleotide binding activity were examined in nuclear extracts from freshly isolated human chondrocytes, from chondrocytes that had been cultured under conditions that allowed the maintenance of a chondrocyte-specific phenotype on plastic dishes coated with the hydrogel poly(2-hydroxyethyl methacrylate), and from chondrocytes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 33 publications
0
40
2
Order By: Relevance
“…26; this study). However, this finding is not in agreement with a previous study showing that Sp1 binding activity was increased during in vitro de-differentiation of human chondrocytes (42). The discrepancy could be due to the fact that we use another cellular model.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…26; this study). However, this finding is not in agreement with a previous study showing that Sp1 binding activity was increased during in vitro de-differentiation of human chondrocytes (42). The discrepancy could be due to the fact that we use another cellular model.…”
Section: Discussioncontrasting
confidence: 56%
“…The fact that Sp1 expression is altered in the de-differentiating chondrocytes (26,42) also reinforces the presumption that Sp1 could be another key factor for induction and/or maintenance of COL2A1 gene expression. In this study, we analyzed the respective role of Sp1 and Sp3 transcription factors in the regulation of COL2A1 gene expression in RAC.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…One of interesting findings of this study is that c-Jun/AP-1 signaling appears to mediate dedifferentiation of chondrocytes caused by IL-1␤, RA, or EGF, whereas dedifferentiation of chondrocytes caused by the serial monolayer subculture on plastic was found to be independent of c-Jun/AP-1. Indeed, it has been suggested that activation of the Sp-1 transcription factor is associated with subculture-induced dedifferentiation of chondrocytes (41), suggesting that Sp-1 and AP-1 may regulate different pathways of chondrocyte dedifferentiation.…”
Section: C-jun In Chondrocyte Dedifferentiationmentioning
confidence: 99%
“…Silencer elements are located in the regions Ϫ300 to Ϫ400 and Ϫ620 to Ϫ700 bp 1 that are believed to function in inhibiting synthesis of type II collagen in nonchondrocytes (16). In addition, Sp1 binding sites in the proximal promoter are believed to be important for efficient enhancer-mediated transcription (17) and Sp1 binding activity differs between differentiated and dedifferentiated chondrocytes (18). Although it has been reported that a fragment from the first intron enhancer can direct chondrocyte-specific expression through a heterologous promoter (12), it is likely that in vivo, the endogenous Col2a1 promoter also participates in gene regulation during certain developmental stages and in response to specific regulatory signals.…”
mentioning
confidence: 99%